2015
DOI: 10.1103/physrevb.91.245105
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation of organic photovoltaic materialsC60, C70, [C60]PCBM, and bis-

Abstract: We present a first-principles investigation of the excited-state properties of electron acceptors in organic photovoltaics including C60, C70, [6,6]-phenyl-C61-butyric-acid-methyl-ester ([C60]PCBM), and bis-[C60]PCBM using many-body perturbation theory within the Hedin's G0W0 approximation and an efficient Lanczos approach. Calculated vertical ionization potentials (VIP) and vertical electron affinities (VEA) of C60 and C70 agree very well with experimental values measured in gas phase. The density of states o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…We take the atomic coordinates from Ref. 24 and choose the PBE exchange and correlation functional 25 for the starting DFT calculation together with a norm-conserving pseudo-potential 26 . The cubic simulation cell has an edge of 40 Bohr and the Coulomb interaction is truncated at 20 Bohr.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…We take the atomic coordinates from Ref. 24 and choose the PBE exchange and correlation functional 25 for the starting DFT calculation together with a norm-conserving pseudo-potential 26 . The cubic simulation cell has an edge of 40 Bohr and the Coulomb interaction is truncated at 20 Bohr.…”
Section: Validationmentioning
confidence: 99%
“…In Ref. 24 we investigated the GW quasi-particle energy levels finding a self-consistent HOMO-LUMO (electronic) gap of 4.94 eV (1.78 eV at the PBE level) and we consider the corresponding scissor operator in the BSE calculation. A basis of 2000 elements is used for representing the static polarisability operator 18,19 .…”
Section: Validationmentioning
confidence: 99%
“…71 To allow for a direct comparison with the GW calculations from Refs. 17,18,23 , the molecular geometries (see Figure 1) were optimized using the PBE functional 72 and 6-31G(d,p) basis set. The optimization of the rangeseparation parameter ω was performed based on the LC-ωPBE 46, 73 functional and using the efficient "golden-ratio" algorithm, as described in our previous work 48,57 (see Supporting…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…20 This method has been shown to 5 provide quantitative predictions for the quasi-particle (QP) spectrum of organic and inorganic systems. 18,[21][22][23][24] However, not only is GW computationally much more demanding than DFT, the fact that it is typically employed non-self-consistently also leads to a significant starting-point dependence. [25][26][27][28][29][30][31] For the case of the pentacene molecule, for example, it has been found that nonself-consistent G 0 W 0 calculations based on a (semi-)local DFT starting point underestimate the fundamental gap E g in the gas phase by as much as 0.7 eV, while E g calculated at the same level of theory for the pentacene crystal are found in good agreement with the experimentally determined solid-state E g , likely due to a fortuitous cancelation of errors.…”
mentioning
confidence: 99%
“…(3), (4), (5), (7) and (8) and summarized in Table 5: The calculated values of IP and EA for all molecules range from 5.497 eV to 6.224 eV and 1.710 eV to 2.191 eV respectively (see table 5). It was found from previous research studies that raising the LUMO energy level of such systems causes the EA to increase and leads to a higher value of Voc [56]. So, we found that the presence of Thiophene and Benzothiadiazole substituents on the systems can increase the EA compared with the other compounds.…”
Section: Uv/vis Absorption Spectramentioning
confidence: 54%